Uganda’s Debt Sustainability: Testing The Efficacy of Debt Overhang Theory - Musiita, Benjamin; Kijjambu, Fredrick Nsambu; Katarangi, Asaph Kabuura; Kahangane, Geoffrey; Akampwera, Sheilla (Journal of Economics and Behavioral Studies, 2023)
The primary objective of this paper is to discern the impact of key economic variables, including primary balance, real interest rate, GDP growth rate, real effective exchange rate, and current account balance, on the long-term and short-term sustainability of the country’s debt. Drawing on an array of econometric analyses within the Auto Regressive Distributed Lag framework, the study establishes that a fiscal surplus and sound management positively influence debt sustainability in the long run. However, it reveals that higher real interest rates pose challenges, leading to increased debt loads. While GDP growth’s impact remains inconclusive, a fluctuating real effective exchange rate and the influence of the current account balance on debt dynamics emerge as crucial determinants. The study recommends a cautious fiscal approach, interest rate management, economic growth stimulation, exchange rate stability, and a focus on achieving and maintaining current account surpluses as pivotal strategies for ensuring Uganda’s long-term debt sustainability. Nonetheless, the study acknowledges limitations related to sample size and endogeneity, encouraging further research to enhance generalizability and address potential omitted variables.